Dynamics of Operational Efficiency, Company Growth, and Financial Performance in the Indonesian Pharmaceutical Industry - Tabah Rizki; Restu Hanin Annisaa (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2026)
The purpose of this study is to analyze the influence of operational efficiency and company growth on the financial performance of pharmaceutical companies in Indonesia. This study uses a descriptive quantitative method with secondary data from the financial statements of pharmaceutical companies listed on the Indonesia Stock Exchange during the period 2021–2024, with a total of 60 observations. Data analysis was conducted to examine the relationship between two independent variables, namely operational efficiency and company growth, with the dependent variable, financial performance. The results of this study indicate that operational efficiency has a positive and significant effect on financial performance, meaning that a company's good mastery of internal resources is a key factor in increasing profitability. This is in line with the Resource-Based View perspective, which views internal capabilities and company-specific assets as sources of competitive advantage. In addition, company growth, measured by sales growth, also has a positive and significant effect on financial performance. These findings support the significance of profitability assumed in Signal Value Theory, which states that a safe signal can be used to assess the future performance of pharmaceutical companies. From this perspective, the profitability of a pharmaceutical company reflects the success of innovation, market productivity, and responsiveness to it. In conclusion, this study provides a theoretical contribution by linking RBV and Signal Theory to the financial performance of pharmaceutical companies, as well as practical implications for investment management and policymakers in efficiency and growth.